Environmentalization of Agriculture in Russia and the World - POLUSHKINA, Tatyana Mihailovna; KOVALENKO, Elena Georgievna; AKIMOVA, Yulia Alekseevna; KOCHETKOVA, Svetlana Andreevna (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017, 2017)
Several decades ago, the world community realized the importance and significance of the ecological component of economics for the quality of life of the population. Almost all developed countries and unions have been prioritizing the ecological factor in the context of building up a new paradigm of economic development, including the agricultural sector. It has become clear that the quality of nutrition, the quality of the environment, and the sustainability of the long-term development ultimately determine the public health. Over the last years, the Russian academic community has also been discussing these issues. In this context, the economic science is now facing a challenge of giving grounds for the theoretical concepts and methodological approaches to the development of a novel, ecologically-oriented agricultural policy of the Russian Federation, to the search for the optimal forms and methods of the state influence on the agricultural sector to promote its environmentalization, to developing a new system of interactions between the authorities, businesses, and farmers, based on the highest possible coordination of the novel mechanisms of state control for the development of the agricultural sector with the motivational framework of the rural population, in relation to the adaptation of the manufacturers of agricultural goods to the modern methods and instruments of state control, enhancing the role of the ecological component in the agricultural sector. This paper substantiates the urge for the development of the system of state control for the agricultural sector of Russian economics in the context of its environmentalization and promotion of the organic agriculture.